Multicenter Validation of the max‐ICH Score in Intracerebral Hemorrhage. Issue 3 (21st December 2020) - Sembill, Jochen A.; Castello, Juan P.; Sprügel, Maximilian I.; Gerner, Stefan T.; Hoelter, Philip; Lücking, Hannes; Doerfler, Arnd; Schwab, Stefan; Huttner, Hagen B.; Biffi, Alessandro; Kuramatsu, Joji B.
Abstract : Objective: Outcome prognostication unbiased by early care limitations (ECL) is essential for guiding treatment in patients presenting with intracerebral hemorrhage (ICH). The aim of this study was to determine whether the max‐ICH (maximally treated ICH) Score provides improved and clinically useful prognostic estimation of functional long‐term outcomes after ICH. Methods: This multicenter validation study compared the prognostication of the max‐ICH Score versus the ICH Score regarding diagnostic accuracy (discrimination and calibration) and clinical utility using decision curve analysis. We performed a joint investigation of individual participant data of consecutive spontaneous ICH patients (n = 4, 677) from 2 retrospective German‐wide studies (RETRACE I + II; anticoagulation‐associated ICH only) conducted at 22 participating centers, one German prospective single‐center study (UKER‐ICH; nonanticoagulation‐associated ICH only), and 1 US‐based prospective longitudinal single‐center study (MGH; both anticoagulation‐ and nonanticoagulation‐associated ICH), treated between January 2006 and December 2015. Results: Of 4, 677 included ICH patients, 1, 017 (21.7%) were affected by ECL (German cohort: 15.6% [440 of 2, 377]; MGH: 31.0% [577 of 1, 283]). Validation of long‐term functional outcome prognostication by the max‐ICH Score provided good and superior discrimination in patients without ECL compared with the ICH Score (area under the receiver operating curve [AUROC], German cohort: 0.81 [0.78–0.83] vs 0.74 [0.72–0.77], p  < 0.01; MGH: 0.85 [0.81–0.89] vs 0.78 [0.74–0.82], p  < 0.01), and for the entire cohort (AUROC, German cohort: 0.84 [0.82–0.86] vs 0.80 [0.77–0.82], p  < 0.01; MGH: 0.83 [0.81–0.85] vs 0.77 [0.75–0.79], p  < 0.01). Both scores showed no evidence of poor calibration. The clinical utility investigated by decision curve analysis showed, at high threshold probabilities (0.8, aiming to avoid false‐positive poor outcome attribution), that the max‐ICH Score provided a clinical net benefit compared with the ICH Score (14.1 vs 2.1 net predicted poor outcomes per 100 patients). Interpretation: The max‐ICH Score provides valid and improved prognostication of functional outcome after ICH. The associated clinical net benefit in minimizing false poor outcome attribution might potentially prevent unwarranted care limitations in patients with ICH. ANN NEUROL 2021;89:474–484